Upaya Meningkatkan Self Confidence Melalui Konseling Kelompok (Studi Pada Residen Narkoba Di Perkumpulan PEKA Medan) - Angelica Banjarnahor; Agus Suriadi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The problems faced by drug residents are not far from the reduced level of self-confidence because they feel worthless. The target to be achieved is to increase self-confidence by drug residents so that they can return to carrying out their social functions again and focus on their strengths and be able to continue the plans that will be implemented after leaving rehabilitation. The solutions offered in this group work practicum are counseling, sharing and providing motivation as well as planning activities to be carried out after rehabilitation so that the client feels he is able to return to the community. The Intervention Program used in this practicum is the Mezzo Intervention by Zastrow which consists of; Preparation (with a Non-Directive Approach), Intake/Engagement, Assessment, Planning, Implementation and Action Plan, Evaluation and Termination